Transcriptomic data on the transgenerational exposure of the keystone amphipod Gammarus locusta to simvastatin - Teresa Neuparth; André M. Machado; Rosa Montes; Rosario Rodil; Susana Barros; Nélson Alves; Raquel Ruivo; Luis Filipe C. Castro; José B. Quintana; Miguel M. Santos (Data in Brief, 2020)
The use of transcriptomics data brings new insights and works as a powerful tool to explore the molecular mode of action (MoA) of transgenerational inheritance effects of contaminants of emerging concern. Therefore, in this dataset, we present the transcriptomic data of the transgenerational effects of environmentally relevant simvastatin levels, one of the most prescribed human pharmaceuticals, in the keystone amphipod species Gammarus locusta. In summary, G. locusta juveniles were maintained under simvastatin exposure up to adulthood (exposed group - F0E) and the offspring of F0E were transferred to control water for the three subsequent generations (transgenerational group - F1T, F2T and F3T).To gain insights into the biological functions and canonical pathways transgenerationally disrupted by simvastatin, a G. locusta de novo transcriptome assembly was produced and the transcriptomic profiles of three individual G. locusta females, per group, over the four generations (F0 to F3) - solvent control groups (F0.C, F1.C, F2.C and F3.C), F0 320 ng/L simvastatin exposed group (F0.320E) and F1 to F3 320 transgenerational group (F1.320T; F2.320T and F3.320T) - were analyzed. Briefly, Illumina HiSeq™ 2500 platform was used to perform RNA sequencing, and due to the unavailability of G. locusta genome, the RNA-seq datasets were assembled de novo using Trinity and annotated with Trinotate software. After assembly and post-processing steps, 106093 transcripts with N50 of 2371 bp and mean sequence length of 1343.98 bp was produced. BUSCO analyses showed a transcriptome with gene completeness of 97.5 % Arthropoda library profile. The Bowtie2, RSEM and edgeR tools were used for the differential gene expression (DEGs) analyses that allowed the identification of a high quantity of genes differentially expressed in all generations. Finally, to identify the main metabolic pathways affected by the transgenerational effects of SIM across all generations, the DGEs genes were blasted onto KEGG pathways database using the KAAS webserver. The data furnished in this article allows a better molecular understanding of the transgenerational effects produced by simvastatin in the keystone amphipod G. locusta and has major implications for hazard and risk assessment of pharmaceuticals and other emerging contaminants. This article is related to the research article entitled “Transgenerational inheritance of chemical-induced signature: a case study with simvastatin [1].